Influence of Workplace Spirituality and Perceived Organizational Support on Organizational Citizenship Behavior Mediated by Organizational Commitment on BPBD Employees of Bengkulu Province - Akbar, Alif Putra (Universitas Bengkulu, 2024)
The type of research used is quantitative research, where there is hypothesis testing. The method of collecting this research is primary data by distributing questionnaires offline. From distributing the questionnaires, 124 respondents from 128 samples were obtained because 4 questionnaires were not returned. Then the data obtained were analyzed in this study using SmartPLS4. This research was conducted to examine (1) the effect of workplace spirituality on organizational citizenship behavior (2) the effect of perceived organizational support on organizational citizenship behavior (3) the effect of organizational commitment on organizational citizenship behavior (4) the effect of workplace spirituality on organizational commitment (5) the effect of perceived organizational support on organizational commitment (6) effect of workplace spirituality on organizational citizenship behavior mediated by organizational commitment (7) effect of perceived organizational support on organizational citizenship behavior mediated by organizational commitment. The conclusion in this study is that workplace spirituality and perceived organizational support on organizational citizenship behavior mediated by organizational commitment show a positive and significant influence. Suggestions for BPBD Bengkulu Province are that it is necessary to increase collaboration with fellow employees, improve facilities and provide rewards for employees and provide comfort for BPBD Bengkulu Province employees.